Merantau in The Ethnic Tradition of Minangkabau: Local Custom Without Sharia Basis? - Siregar, Fatahuddin Aziz; Yulika, Febri; Nofialdi, Nofialdi; Harahap, Ikhwanuddin; Ridwan, Benny; Syahputra, Iswandi (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
Customary practice in Minangkabau is based on sharia, and sharia is based on the Qur’an (as provisioned in the proverb Adat Bersandi Syarak, Syarak Bersandi Kitabullah-ABS/SBK). As a customary practice, is merantau in the Minangkabau tradition based on sharia? This article explains the relationship between custom and sharia in Minangkabau’s merantautradition. This study is a qualitative research with in-depth interview data collection techniques and literature study. In-depth interviews were conducted with four distinct individuals representing customary figures and religious figures of West Sumatra. The study found that merantau in the Minangkabau tradition emerged out of the matrilineal customary system that has been in place long before Islam was introduced to the Minangkabau community. As a custom, several aspects of merantau in the Minang culture contradict Islamic sharia. This indicates that the relationship between custom and sharia is not hierarchical as stipulated in the ABS/SBK model. The study results may have implications on new relations between customary law, sharia, culture, and religion.